Central metabolic responses to the overproduction of fatty acids in Escherichia coli based on 13C‐metabolic flux analysis. Issue 3 (31st October 2013) - He, Lian; Xiao, Yi; Gebreselassie, Nikodimos; Zhang, Fuzhong; Antoniewicz, Maciek R.; Tang, Yinjie J.; Peng, Lifeng
ABSTRACT We engineered a fatty acid overproducing Escherichia coli strain through overexpressing tesA ("pull") and fadR ("push") and knocking out fadE ("block"). This "pull‐push‐block" strategy yielded 0.17 g of fatty acids (C12–C18) per gram of glucose (equivalent to 48% of the maximum theoretical yield) in batch cultures during the exponential growth phase under aerobic conditions. Metabolic fluxes were determined for the engineered E. coli and its control strain using tracer ([1, 2‐13C]glucose) experiments and 13C‐metabolic flux analysis. Cofactor (NADPH) and energy (ATP) balances were also investigated for both strains based on estimated fluxes. Compared to the control strain, fatty acid overproduction led to significant metabolic responses in the central metabolism: (1) Acetic acid secretion flux decreased 10‐fold; (2) Pentose phosphate pathway and Entner–Doudoroff pathway fluxes increased 1.5‐ and 2.0‐fold, respectively; (3) Biomass synthesis flux was reduced 1.9‐fold; (4) Anaplerotic phosphoenolpyruvate carboxylation flux decreased 1.7‐fold; (5) Transhydrogenation flux converting NADH to NADPH increased by 1.7‐fold. Real‐time quantitative RT‐PCR analysis revealed the engineered strain increased the transcription levels of pntA (encoding the membrane‐bound transhydrogenase) by 2.1‐fold and udhA (encoding the soluble transhydrogenase) by 1.4‐fold, which is in agreement with the increased transhydrogenation flux. Cofactor and energy balances analyses showed that the fatty acid overproducing E. coli consumed significantly higher cellular maintenance energy than the control strain. We discussed the strategies to future strain development and process improvements for fatty acid production in E. coli. Biotechnol. Bioeng. 2014;111: 575–585. © 2013 Wiley Periodicals, Inc.